2020
DOI: 10.1080/17518253.2020.1839572
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional green silver nanoparticles in pharmaceutical and biomedical applications

Abstract: The present study concerned with the use of an aqueous ginger extract as naturally and ecofriendly reducing and stabilizing agent in the synthesis of silver nanoparticles (AgNPs). The unique physicochemical characteristics of green synthesized AgNPs exhibit high potential antimicrobial activity and displayed an impact role in pharmaceutical determinations. To confirm the nanoscale of green synthesized AgNPs, various microscopic and spectroscopic techniques were performed. The synthesized nanoparticles were scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The use of Cocos nucifera in the green synthesis of AgNPs has been described previously by Uddin et al 85 It can be noted from the results that three significant peaks occurred in the spectra at 3450, 1645, and 1089 cm –1 . Furthermore, Al Masoud et al 86 demonstrated the use of FTIR to detect biomolecules for reducing Ag + ions and capping the ginger-extract-produced bioreduced AgNPs ( Figure 7 ). The findings from this study showed that the functional groups can be detected from the synthesized AgNPs, and significant peaks can be detected at 1057, 1386, 1620, and 3417 cm –1 , which corresponded to primary alcohols and NO 3 , and C–N stretching vibrations of aliphatic and aromatic amines, respectively, can be detected.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of Cocos nucifera in the green synthesis of AgNPs has been described previously by Uddin et al 85 It can be noted from the results that three significant peaks occurred in the spectra at 3450, 1645, and 1089 cm –1 . Furthermore, Al Masoud et al 86 demonstrated the use of FTIR to detect biomolecules for reducing Ag + ions and capping the ginger-extract-produced bioreduced AgNPs ( Figure 7 ). The findings from this study showed that the functional groups can be detected from the synthesized AgNPs, and significant peaks can be detected at 1057, 1386, 1620, and 3417 cm –1 , which corresponded to primary alcohols and NO 3 , and C–N stretching vibrations of aliphatic and aromatic amines, respectively, can be detected.…”
Section: Introductionmentioning
confidence: 99%
“… Infrared spectra of ginger extract (A) and silver nanoparticles produced using ginger extract (B) (reprinted with permission from ref ( 86 )). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suspension alone is the AgNP suspension (SN). This suspension was then placed on an electric heater and magnetic stirrer at 60° C until a yellowish color was observed, indicating the formation of silver nanoparticles ( AlMasoud et al, 2020v , Alomar et al, 2020 ). This suspension was stored in a conical glass flask covered with foil at room temperature until use, as studies show the suspension remains stable under these conditions ( AlMasoud et al, 2020v , Alomar et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%